Obraz emigracji rosyjskiej w twórczości Władimira Maksimowa - Siemianowska, Izabella (Acta Polono-Ruthenica, 2018)
Vladimir Maximov in his journalistic writing, prose and dramaturgy has devoted considera- ble attention to the Russian emigration. The writer was interested in emigration as a phenomenon, In his literary output he outlined a picture of an emigration environment which can be referred to as ambiguous. The present article is an attempt at presenting a picture of the Russian emigration seen from the angle of Vladimir Maximov personal experiences, observations and considerations.